Implemetasi Website SD Muhammadiyah 05 Karang Talun Kabupaten Cilacap - Isa Bahroni; Andesita Prihantara; Abdul Rohman Supriyono (Politeknik Negeri Cilacap, 2021)
SD Muhammadiyah 05 Cilacap was established in 1970 in the village of Lomanis Banyusrep South Cilacap, is an educational institution under the leadership of the Muhammadiyah branch of North Cilacap. The curriculum that is taught using the curriculum of the Cilacap Regency Education office has a function of preaching Islam to the community. SD Muhammadiyah 05 is named SD Mulia which is an educational organization that is fixing the information system so that it is easily accessible to the public and widely known by the public so that its activities can support its existence. Request for fast and accurate information at the time of PPDB (New Student Registration) using information and communication technology is very urgent. This time, Community Service, We created an android-based website that can be used as a medium of information and communication to answer problems faced at SD Mulia, with a system that can be accessed using smart phone media.